Factors Affecting Impulse Buying on Online Shopping amongst Youth: A Structural Equation Modeling Approach: Exploring the factors influencing impulse buying on online shopping among youth (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This article aims to identify the constructs that impacts impulse buying on online shoppingamongst youth. The research was conducted based on the response received from 301 responses fromthe youth population. The main significant components consist of scarcity, serendipity, e-commerce,social shopping, value shopping and relaxation shopping. “Factors were identified from literature surveyand exploratory factor analysis was utilized for grouping the variables under different components. Thefindings contributed that the six latent variables are significant contributors to the affective impulsebuying tendency. This was validated using structural equation modeling approach utilizing AMOS 22.0.This research helps to understand the rising trend of e-commerce in the developing country’sprospective. It also develops a foundation for future research and significant insights to perceive theimpulse buying on online shopping amongst youth.